Changing response of the North Atlantic/European Winter Climate to the 11-year solar cycle - Ma, H; Chen, H; Gray, L; Zhou, L; Li, X; Wang, R; Zhu, S (IOP Publishing, 2017)
Recent studies have presented conflicting results regarding the 11-year solar cycle (SC) influences on winter climate over the North Atlantic/European region. Analyses of only the most recent decades suggest a synchronized North Atlantic Oscillation (NAO)-like response pattern to the SC. Analyses of long-term climate data sets dating back to the late 19th century, however, suggest a mslp response that lags the SC by 2-4 years in the southern node of the NAO (i.e. Azores region). To understand the conflicting nature and cause of these time dependencies in the SC surface response, the present study employs a lead/lag multi-linear regression technique with a sliding window of 44-years over the period 1751-2016. Results confirm previous analyses, in which the average response for the whole time period features a statistically significant 2-4-year lagged mslp response centered over the Azores region. Overall, the lagged nature of Azores mslp response is generally consistent in time, with stronger and statistically significant SC signals tend to appear in the periods when the SC forcing amplitudes are relatively larger. Individual month analysis indicates the consistent lagged response in December-January-February average arises primarily from early winter months (i.e. December and January), which is associated with ocean feedback processes that involve reinforcement by anomalies from the previous winter. Additional analysis suggests that the synchronous NAO-like response in recent decades arises primarily from the late winter month (February), possibly reflecting a result of strong internal noise.